Pendekatan induktif untuk meningkatkan kemampuan guru dalam pembelajaran matematika sekolah dasar - S B Kurniawan, A Surya , Sularmi, S Istiyati, dan Hadiyah (Universitas Sebelas Maret, 2020)
Abstract. The purpose of writing this article is to describe: developing models and formulating rough forms of design models of inductive approaches to learning mathematics for elementary school (SD) teachers whose backgrounds are not from mathematics or mathematics education. The research partners are Mutiara Persada Elementary School teachers, Kasihan Subdistrict, Bantul Regency. The research approach is mixed qualitative and quantitative with the type of research and development. Data collection techniques for first year research are using:questionnaires, interviews, and documentation. The development model used is the ADDIE model by Dick & Carry (1996). The results of the study, namely: (1) maximizing mathematical understanding needs to pay attention to Piaget's learning theory, (2) the mistakes made by the teacher are how to make the relationship between symbols and procedures and the availability of appropriate references, linking symbolic procedures with informal problem solving, and connecting between symbol system, (3) inductive message processing, i.e., it starts with facts or special events which are then related to the previous material (prerequisite material), conceptualization based on facts that are in accordance with reasoning and the results of empirical case development, and compilation of generalizations based on concepts concepts, and (4) the construction of a crude model of mathematics learning with an inductive approach, the stages of which are:decomposition of the problem; determination of prerequisite material;fixing the facts of the problem; motor, affective, and cognitive domain integration activities; reasoning process; evaluation of the reasoning process; empirical case development; concept formulation; and evaluation of learning.Keywords: Inductive Approach, Teacher's Ability, Mathematics Learning